phú trần

 Cho biểu thức :B=\(\left(\frac{21}{x^2-9}-\frac{x-4}{3-x}-\frac{x-1}{3+x}\right):\left(1-\frac{1}{x+3}\right)\)

 a) Rút gọn B 

b) Tim x de B =\(\frac{-3}{5}\)

c)Tim x de B<0

Hoàng Thanh Tuấn
1 tháng 6 2017 lúc 22:05
\(B=\left(\frac{21}{\left(x-3\right)\left(x+3\right)}+\frac{\left(x-4\right)\left(x+3\right)}{\left(x-3\right)\left(x+3\right)}-\frac{\left(x-3\right)\left(x-1\right)}{\left(x-3\right)\left(x+3\right)}\right):\frac{x+3-1}{x+3}\)\(=\frac{3x+6}{\left(x-3\right)\left(x+3\right)}.\frac{x+3}{x+2}=\frac{3\left(x+2\right)\left(x+3\right)}{\left(x-3\right)\left(x+3\right)\left(x+2\right)}=\frac{3}{x-3}\)Điều kiện \(x\ne3\) \(\Rightarrow\frac{-3}{5}=\frac{3}{x-3}\Leftrightarrow x-3=-5\Leftrightarrow x=-2\)\(B=\frac{3}{x-3}< 0\Leftrightarrow x-3< 0\Leftrightarrow x< 3\)
Hương
1 tháng 6 2017 lúc 22:23

a) B=(\(\frac{21}{x^2-9}\)-\(\frac{x-4}{3-x}\)-\(\frac{x-1}{3+x}\)) : (1-\(\frac{1}{x+3}\)) (ĐK: x khác +-3)

=(\(\frac{21}{\left(x-3\right).\left(x+3\right)}\)+\(\frac{x-4}{x-3}\)-\(\frac{x-1}{x+3}\)) : (1-\(\frac{1}{x+3}\))

=(\(\frac{21+\left(x+4\right).\left(x+3\right)-\left(x-1\right).\left(x-3\right)}{\left(x-3\right).\left(x+3\right)}\):(\(\frac{x+3-1}{x+3}\))

=(\(\frac{3x+6}{\left(x-3\right).\left(x+3\right)}\)) . (\(\frac{x+3}{x+2}\))

=(\(\frac{3.\left(x+2\right)}{\left(x-3\right).\left(x+3\right)}\)\(\frac{x+3}{x+2}\)

=\(\frac{3}{x-3}\)

b) B=\(\frac{3}{x-3}\)=\(\frac{-3}{5}\)

(=) \(\frac{3.5}{x-3}\)=-3

(=) -3.(x-3) = 15

(=) -3x=6

(=) x=-2

vậy x=2 thì B=\(\frac{-3}{5}\)

c) B=\(\frac{3}{x-3}\)<0

(=) 3 < x - 3

(=) -x < - 3 - 3

(=) x > 6

Vậy với x > 6 thì B < 0

๖Fly༉Donutღღ
6 tháng 2 2018 lúc 17:18

\(B=\left(\frac{21}{x^2-9}-\frac{x-4}{3-x}-\frac{x-1}{x+3}\right):\left(1-\frac{1}{x+3}\right)\)

\(B=\left[\frac{21}{\left(x-3\right)\left(x+3\right)}+\frac{\left(x-4\right)\left(x+3\right)}{\left(x-3\right)\left(x+3\right)}-\frac{\left(x-1\right)\left(x-3\right)}{\left(x+1\right)\left(x+3\right)}\right]\)    \(:\left[\frac{x+3-1}{x+3}\right]\)

\(B=\frac{21+x^2-x-12-x^2+4x-3}{\left(x-3\right)\left(x+3\right)}:\frac{x+2}{x+3}\)

\(B=\frac{3x+6}{\left(x-3\right)\left(x+3\right)}.\frac{x+3}{x+2}\)

\(B=\frac{3.\left(x+2\right)}{\left(x-3\right)\left(x+3\right)}.\frac{x+3}{x+2}\)

\(B=\frac{3}{x-3}\)

b)   \(B=\frac{-3}{5}\Leftrightarrow\frac{3}{x-3}=\frac{-3}{5}\)

\(\Leftrightarrow-3x+9=15\)

\(\Leftrightarrow-3x=6\)

\(\Leftrightarrow x=-2\)

vậy....

c) \(B< 0\Leftrightarrow\frac{3}{x-3}< 0\)

\(\Leftrightarrow x-3< 0\)   vì \(3>0\)

\(\Leftrightarrow x< 3\)

vậy....


Các câu hỏi tương tự
phu tran
Xem chi tiết
phú trần
Xem chi tiết
Nguyễn Thị Bảo Trâm
Xem chi tiết
Nguyễn Diệu Linh
Xem chi tiết
Đỗ Minh Anh
Xem chi tiết
Trần Hà Trang
Xem chi tiết
Phạm Tiến	Dũng
Xem chi tiết
Momozono Nanami
Xem chi tiết
anh phuong
Xem chi tiết